Morphological and phytochemical characterization of susceptible and resistant sengon (Falcataria moluccana) tree to gall rust disease - DEWI RAHMAWATI; NURUL KHUMAIDA; ULFAH J SIREGAR (Society for Indonesian Biodiversity, 2019)
Abstract. Rahmawati D, Khumaida N, Siregar UJ. 2019. Morphological and phytochemical characterization of susceptible and resistant sengon (Falcataria moluccana) tree to gall rust disease. Biodiversitas 20: 907-913. Gall rust disease has severely attacked sengon tree (Falcataria moluccana Miq. Barneby & J.W. Grimes)) and it rapidly spread in tree plantations causing the decrease of wood productivity. Although sengon is widely cultivated in several areas in Indonesia, there are limited studies on secondary metabolite composition of its wood. This research was aimed to study differences on morphology, wood anatomy and secondary metabolites content of resistant and susceptible sengon tree trunk to gall rust disease. Both resistant and susceptible tree samples to gall rust were selected from the same plantation plots to minimize environmental effects. Structure of wood samples was observed using Scanning Electron Microscope (SEM) JSM-5310LV. Seven types of secondary metabolites, i.e., alkaloids, flavonoids, saponins, phenolic hydroquinones, tannins, triterpenoids, and steroids were qualitatively analyzed from powdered wood samples. Based on field observations, the gall rust fungi changed the color, texture, pores of the tree surface and decreased wood density. In microscopic observations, sengon trunk, which is resistant to gall rust disease, showed organized and regularly structured wood anatomy and did not show hyphae of the infecting fungi inside the wood. The fungi damaged susceptible sengon trunk as indicated by the dispersed and irregular structure of wood tissue, while the presence of fungal hyphae among wood cells was detected. Phytochemical analyses indicated that trunk of sengon containing flavonoids, saponins, phenolic hydroquinones, tannins, triterpenoids, and steroids, except alkaloids. Sengon trunk, which is resistant to gall rust disease, had stronger reactions of flavonoids, saponins, triterpenoids, and steroids compared to that susceptible one.